2021
DOI: 10.7759/cureus.18783
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic miR-204 Induces Alteration of Heart Electrophysiology and Neurogenic Hypertension by Regulating the Sympathetic Nerve Activity: Potential Role of Microbiota

Abstract: There is abundant evidence demonstrating the association between gut dysbiosis and neurogenic diseases such as hypertension. A common characteristic of resistant hypertension is the chronic elevation in sympathetic nervous system (SNS) activity accompanied by increased release of norepinephrine (NE), indicating a neurogenic component that contributes to the development of hypertension. Factors that modulate the sympathetic tone to the cardiovascular system in hypertensive patients are still poorly understood. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Through a variety of pathways, the gut microbiota could significantly regulate the development of cardiac arrhythmias, which may provide an extensive range of possible therapeutic approaches [ 58 , 59 ]. For example, experimental evidence has indicated a bidirectional relationship between alterations in the categories of bacteria present in the gut and neurogenic diseases, including hypertension, which might also function as a molecular dispatch that could convert gut bacterial signals into a neural yield that could also influence hypertension and/or cardiac electrophysiology [ 58 ]. In addition, it has been suggested that the role of the gut microbiota and its metabolites might be involved in the pathogenesis as well as the prognostic value of many cardiovascular diseases [ 59 ].…”
Section: Gut Microbiota and Cardiac Arrhythmiamentioning
confidence: 99%
See 2 more Smart Citations
“…Through a variety of pathways, the gut microbiota could significantly regulate the development of cardiac arrhythmias, which may provide an extensive range of possible therapeutic approaches [ 58 , 59 ]. For example, experimental evidence has indicated a bidirectional relationship between alterations in the categories of bacteria present in the gut and neurogenic diseases, including hypertension, which might also function as a molecular dispatch that could convert gut bacterial signals into a neural yield that could also influence hypertension and/or cardiac electrophysiology [ 58 ]. In addition, it has been suggested that the role of the gut microbiota and its metabolites might be involved in the pathogenesis as well as the prognostic value of many cardiovascular diseases [ 59 ].…”
Section: Gut Microbiota and Cardiac Arrhythmiamentioning
confidence: 99%
“…As mentioned before, miR-122-5p could possess great diagnostic potential in arrhythmogenic cardiomyopathy patients [40,57] (Figure 2). yield that could also influence hypertension and/or cardiac electrophysiology [58]. In a dition, it has been suggested that the role of the gut microbiota and its metabolites mig be involved in the pathogenesis as well as the prognostic value of many cardiovascul diseases [59].…”
Section: Gut Microbiota and Cardiac Arrhythmiamentioning
confidence: 99%
See 1 more Smart Citation
“…Impaired vasorelaxation is a marker for early atherosclerosis, and it is proposed that phosphorylated STAT3, a repressor of miR-204, is a potential gut–heart signaling target as it was subsequently downregulated in mice with high-fat diets, though it is potentially not the only target, as Sirt1 knockout did not completely ameliorate miR-204 upregulation. Gut dysbiosis may also impact hypothalamic miR-204, as studies show an association between decreased hypothalamic miR-204 and increased hypothalamic brain-derived naturopathic factor (BDNF) [ 64 ]. Increased BDNF in the hypothalamic paraventricular nucleus is associated with arrhythmia, hypertension, and sympathetic activity, which indicates that gut dysbiosis may alter cardiovascular activity through indirect neurogenic pathways.…”
Section: Mirnas In the Pathogenesis Of Complications Associated With Ibdmentioning
confidence: 99%
“…The gut and brain also display remotely mediated crosstalk, as Jang et al showed that fecal microbiota transplant (FMT) from patients with IBD with or without depression significantly increased anxiety-like behaviors within mice, and mice transplanted with FMTs from patients with IBD and depression showed depression-like behaviors as well [ 71 ]. There is also evidence that IBD can facilitate organizational changes within neurological structures, which could be mediated by miRNAs [ 64 ].…”
Section: Mirnas In the Pathogenesis Of Complications Associated With Ibdmentioning
confidence: 99%